Does Data Disclosure Improve Local Government Performance? Evidence from Italian Municipalities - Ben Lockwood; Francesco Porcelli; Michela Redoano; Antonio Schiavone (Center for Economic Studies and ifo Institute (CESifo), 2022)
We exploit the introduction of an open data online platform - part of a transparency program initiated by the Italian Government in late 2014 - as a natural experiment to analyse the effect of data disclosure on mayors' expenditure and public good provision. First, we analyse the effect of the program by comparing municipalities on the border between ordinary and special regions, exploiting the fact that the latter regions did not participate in the program. We find that mayors in ordinary regions immediately change their behaviour after data disclosure by improving the disclosed indicators, and that the reaction depends also on their initial relative performance, a yardstick competition effect. Second, we investigate the effect of mayors' attention to data disclosure within treated regions by tracking their daily accesses to the platform, which we instrument with the daily publication of newspaper articles mentioning the program. We find that mayors react to data disclosure by decreasing spending via a reduction of service provision, resulting in an aggregate decrease in efficiency. Overall, mayors seem to target variables that are disclosed on the website at the expense of variables that are less salient.
Keywords: H72; H79; 330; open data; local government; media coverage; OpenCivitas